Hybrid photo‐receiver based on SiGe heterojunction photo‐transistor for low‐cost 60 GHz intermediate‐frequency radio‐over‐fibre applications. Issue 8 (1st April 2015) - Viana, C.; Tegegne, Z.G.; Rosales, M.; Polleux, J.L.; Algani, C.; Lecocq, V.; Lyszyk, C.; Denet, S.
Abstract : The first results of an integrated hybrid photo‐receiver based on a 850 nm two‐terminal (2T) silicon germanium (SiGe) heterojunction bipolar photo‐transistor (HPT) for low‐cost radio‐over‐fibre (RoF) applications is presented. A hybrid module was realised with two cascaded low‐noise amplifiers of 20 dB total gain and an SiGe 2T‐HPT exhibiting a −15 dB opto‐microwave gain at 5.15 GHz with a 1.6 GHz bandwidth. A 16% degradation of the error vector magnitude compared with back‐to‐back measurement for the transmission of a 2 GHz OFDM signal at 3 Gbit/s was measured based on the 60 GHz IEEE 802.15.3c standard transposed at the intermediate frequency (IF) of 5 GHz, according to an IF‐RoF distribution mode.